Cálculo y estudio de parámetros en instalación de interruptores de potencia con gas SF6 para evitar daños por fallas a transformadores de poder en subestaciones típicas de CNEL Unidad de Negocios Guayaquil. - Coello Aquino, Freddy Simón (2019)
CNEL EP is a benchmark in the country's electricity sector, to solve situations of overload or short circuits, using switches that interrupt the flow of fault current in equipment and / or systems, so this research seeks to "Determine the parameters for the installation of power switches with SF6 gas to avoid damage due to faults, to power transformers in typical substations ". First of all, the devices that protect the electric circuits against damages due to alterations in the current are studied theoretically, to know the operation of power switches that use gas with SF6 technology for the extinction of the electric arc; then a comparative study has been developed, of the power devices with SF6 gas that protect the electric circuits in typical substations of CNEL, Guayaquil Business Unit, 150e and 200e S & C fuses and Alstom DT1-72.5, Siemens 3AP1 FG 145 kV and 245 kV, and ABB 72 PM40-C; Finally, we propose a more adequate solution regarding the installation of power switches with SF6 gas, aimed at minimizing the damage caused by faults to power transformers. The research has had a qualitative and quantitative approach, and is descriptive and exploratory in nature.